Five Basic Steps to Successful Perennial Pasture Grass Establishment From Vegetative Cuttings on South Florida Flatwoods - Joe Vendramini; Yoana Newman; Ann Blount; Martin B. Adjei; Paul Mislevy (EDIS)
Revised! SSAGR24, a 4-page illustrated fact sheet by Joe Vendramini, Yoana Newman, Ann Blount, Martin B. Adjei, and Paul Mislevy, describes the different steps that minimize establishment failure and lead to a favorable outcome of dense stand of perennial pasture grass. Published by the UF Department of Agronomy, March 2010.